THE EFFECTS OF THE DEVELOPMENT OF THE NATURAL GAS INDUSTRY ON THE GLOBAL OIL MARKETS - Dr: Nassif Jassim Ali Al-ebadi (Scholar Express Journals, 2025)
Global energy markets are witnessing rapid and continuous changes due to the multiplicity of factors affecting them, and these changes have a reflection on energy-related industries, such as the oil, natural gas, and coal industries. Recent attention is focused on the natural gas industry, especially during the past five decades. Finding a gas well was previously considered a failed and often neglected exploration, while now it is a major achievement because natural gas has taken a leading position in the energy ladder, after oil and coal for its economic properties and environmental This led to an increase in investments in the field of the natural gas industry, and intensified competition between countries to develop this industry and increase its revenues as an alternative to other economic aspects. The research discusses in a focused way the composition of natural gas and its treatment method, with reference to the advanced technology used, which pushed the development of this industry forward. This had an impact on the oil market, where there is an inverse relationship between the prices of energy sources Natural gas is expected to occupy a leading position during which it will be a successful alternative to oil and these developments will affect the oil markets.
Keywords: Natural Gas Industry; Global Oil Markets; Natural gas markets